(untitled) (Global Journal of Management and Business Research, 2019)
For a brand to be successful, strong brand equity is a core. It is this strength that leads the brand to be prominent in the marketplace and shine amidst its competitors. Good brand equity leads the purchase decision process in which led by purchase intention. Brand equity is vital for any business organization in order to boost up its performance. Therefore, brand equity has affects on the purchase intention of consumers. Moreover, brand equity for a brand is crucial to increase its valuation in the market and to increase its market share. Furthermore, purchase intention is the kind of decision making where a customer buys the same brand repeatedly based on their purchase history. Retaining such a customer is crucial since that customer is likely to shift immediately to another brand due to the high choice availability in today#x2019;s market. The shampoo market as a whole can be identified to be highly fragmented and cluttered with different brands, suppliers, and distribution channels. This research will examine the impact of brand equity on purchase intention of shampoo products in the Colombo region of Sri Lanka. From the findings done by this research, it will be an advantage for the marketers in the industry to execute effective marketing plans and also for future researchers for their research findings.